Hume and Hutcheson on Cicero's 'Proof Against the Stoics'. Issue 2 (June 2017) - Edwards, Jeff
Abstract : This article takes its cue from an intriguing passage in Hume's September 1739 letter to Hutcheson. After appealing to what Cicero proves 'against the Stoics' in book four of De finibus, Hume indicates that he and Hutcheson are in some respect opposed to one another as far as their views on virtue and moral motivation are concerned. While this may seem surprising, given the similarities between their approaches to the foundations of morals, careful analysis of Cicero's criticism of Stoic ethics shows why Hume and Hutcheson should indeed be fundamentally at odds with one another in precisely the respect indicated by Hume.